2022
DOI: 10.1021/acsomega.2c03348
|View full text |Cite
|
Sign up to set email alerts
|

Active Pt-Nanocoated Layer with Pt–O–Ce Bonds on a CeOx Nanowire Cathode Formed by Electron Beam Irradiation

Abstract: A Pt-nanocoated layer (thickness of approx. 10–20 nm) with Pt–O–Ce bonds was created through the water radiolysis reaction on a CeO x nanowire (NW), which was induced by electron beam irradiation to the mixed suspension of K 2 PtCl 4 aqueous solution and the CeO x NW. In turn, when Pt-nanocoated CeO x NW/C (Pt/C ratio = 0.2) was used in the cathode layer of a membrane electrode assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Thanks to its unique property, CeO 2 has been investigated as a promoter of the Pt/C catalyst for enhancing the oxygen concentration on the cathode surface and the ORR catalytic activity, leading to increase low‐temperature fuel cell performances. The enhanced performance obtained with the CeO 2 addition in the cathode layer is also due to the strong interaction between Pt and the oxide particles and to a better stability and durability of the composite catalysts [22–25] . However, it was demonstrated that cerium ions can get soluble in water during fuel cell operation, migrating out of the ionomer or binder, resulting in the loss of scavenging effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to its unique property, CeO 2 has been investigated as a promoter of the Pt/C catalyst for enhancing the oxygen concentration on the cathode surface and the ORR catalytic activity, leading to increase low‐temperature fuel cell performances. The enhanced performance obtained with the CeO 2 addition in the cathode layer is also due to the strong interaction between Pt and the oxide particles and to a better stability and durability of the composite catalysts [22–25] . However, it was demonstrated that cerium ions can get soluble in water during fuel cell operation, migrating out of the ionomer or binder, resulting in the loss of scavenging effect.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced performance obtained with the CeO 2 addition in the cathode layer is also due to the strong interaction between Pt and the oxide particles and to a better stability and durability of the composite catalysts. [22][23][24][25] However, it was demonstrated that cerium ions can get soluble in water during fuel cell operation, migrating out of the ionomer or binder, resulting in the loss of scavenging effect. In addition, these positive cerium ions (Ce 3 + or and Ce 4 + ) in water can establish ionic interaction with the anionic sulfonic groups of the membrane, reducing its proton conductivity.…”
Section: Introductionmentioning
confidence: 99%